Can a Smartphone App for Cannabis Cessation Gain a Broader User Group than Traditional Treatment Services? - John-Kåre Vederhus; Malin Rørendal; Cathrine Bjelland; Anja Kristin Solheim Skar; Øistein Kristensen (SAGE Publishing, 2020)
Background: Treatment demand for cannabis use disorders is increasing in Europe. Mobile phone- and internet-based interventions for cannabis users can possibly help meet the need. The purpose of this study was to examine whether a recently developed Norwegian Cannabis Cessation app reaches a broader or different user group compared to community-based Cannabis Cessation programs (CCP, Nordic abbreviation: HAP). Method: The app respondents (n = 148) were recruited through an online link in the app. A comparative sample (n = 102) was recruited in three municipally based CCPs in Norway. We examined whether app users differed from the CCP population in sociodemographics, substance use, mental health, and well-being. Result: The app group included more women than the CCP group (46% versus 26%, χ 2 = 10.9, P = .001), but otherwise the groups were similar for sociodemographic variables. Severity of cannabis use did not differ between groups, but the app sample exhibited a higher depressiveness score on the Hopkins Symptom Checklist (mean difference, 0.24; 95% CI 0.04-0.44; P = .018) and lower perceived well-being (3.4 point lower score on the Outcome Rating Scale; 95% CI −5.7 to −1.2; P = .003). Well-being was negatively associated with being in the app group, being older, and having higher levels of mental distress, and was positively associated with the perceived ability to make changes ('self-efficacy of quitting'). Conclusion: The higher proportion of women in the app group indicated that the app did capture an expanded segment of the cannabis-using population. The app can be an alternative for those who are not yet prepared to seek treatment in formal healthcare services. The high level of depressive symptoms and lower levels of well-being among the app respondents suggest that some app users might need additional support.